Emission Factors and Importance of PCDD/Fs, PCBs, PCNs, PAHs and PM10 from the Domestic Burning of Coal and Wood in the U.K - Lee, Robert G. M; Coleman, Peter; Jones, Joanne L; Jones, Kevin C; Lohmann, Rainer (Environmental science & technology, 2005)
This paper presents emission factors (EFs) derived for a range of persistent organic pollutants (POPs) when coal and wood were subject to controlled burning experiments, designed to simulate domestic burning for space heating. A wide range of POPs were emitted, with emissions from coal being higher than those from wood. Highest EFs were obtained for particulate matter, PM10, (∼ 10 g/kg fuel) and polycyclic aromatic hydrocarbons (∼ 100 mg/kg fuel for ΣPAHs). For chlorinated compounds, EFs were highest for polychlorinated biphenyls (PCBs), with polychlorinated naphthalenes (PCNs), dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) being less abundant. EFs were on the order of 1000 ng/kg fuel for ΣPCBs, 100s ng/kg fuel for ΣPCNs and 100 ng/kg fuel for ΣPCDD/Fs. The study confirmed that mono- to trichlorinated dibenzofurans, Cl1,2,3DFs, were strong indicators of low temperature combustion processes, such as the domestic burning of coal and wood. It is concluded that numerous PCB and PCN congeners are routinely formed during the combustion of solid fuels. However, their combined emissions from the domestic burning of coal and wood would contribute only a few percent to annual U.K. emission estimates. Emissions of PAHs and PM10 were major contributors to U.K. national emission inventories. Major emissions were found from the domestic burning for Cl1,2,3DFs, while the contribution of PCDD/F-ΣTEQ to total U.K. emissions was minor.